Analysis and trends of hotel development in Ukraine - Ostapenko, Yana Oleksandrivna; Braunahel, A.V. (Житомирська політехніка, 2020)
The activity of the hotel industry is analyzed, the development trend is determined.

Проаналізовано діяльність готельної галузі, визначено тенденцію розвитку.
Keywords: hotel; hotel industry; development trend; tourism; готель; готельне господарство; тенденція розвитку; туризм